2021
DOI: 10.3390/app11114841
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Hyperspectral Imaging (NIR-HSI) for Nondestructive Prediction of Anthocyanins Content in Black Rice Seeds

Abstract: Anthocyanins are an important micro-component that contributes to the quality factors and health benefits of black rice. Anthocyanins concentration and compositions differ among rice seeds depending on the varieties, growth conditions, and maturity level at harvesting. Chemical composition-based seeds inspection on a real-time, non-destructive, and accurate basis is essential to establish industries to optimize the cost and quality of the product. Therefore, this research aimed to evaluate the feasibility of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The R 2 of the prediction model reached 0.80. Amanah et al (2021) used near-infrared hyperspectral imaging to realize the non-destructive detection of anthocyanin content in black rice seeds, and the R 2 of the best prediction model was 0.95. These studies showed that hyperspectral technology had high feasibility in the physiological indexes of crops.…”
Section: Discussionmentioning
confidence: 99%
“…The R 2 of the prediction model reached 0.80. Amanah et al (2021) used near-infrared hyperspectral imaging to realize the non-destructive detection of anthocyanin content in black rice seeds, and the R 2 of the best prediction model was 0.95. These studies showed that hyperspectral technology had high feasibility in the physiological indexes of crops.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the total phenolic content and the spectral data was developed using the least squares method, as given in Equation 4. This technique was recommended for this study since it was successfully used to predict phytochemical compounds in previous studies (Amanah et al, 2021).…”
Section: Model Developmentmentioning
confidence: 99%
“…Aflatoxin has been detected from peanuts using deep learning and HSI (Han and Gao, 2019). The machine learning method has been applied on black rice HSI data to predict the anthocyanin content (Amanah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These fundamental quantitative applications in NIRS have also been effective in NIR-HSI techniques. For example, calibration models were established to quantitate moisture [134], oil [135], anthocyanins [136] and fungal contamination in fruit using quantitative visualization methods [137].…”
Section: Nirs-based Imaging Applications For the Detection Of Chemica...mentioning
confidence: 99%